Perancangan Case Tools untuk Diagram Use Case, Activity, dan Class untuk Permodelan Uml Berbasis Web Menggunakan HTML5 dan PHP - Mohammad Subekti; Lukman Lukman; Donny Indrawan; Ganesh Putra (Bina Nusantara University, 2014)
This study is intended to generate an application tools (CASE tools) that allows a software developer to create a modeling system design using Unified Modeling Language (UML), especially in making use case, activity or class diagrams more quickly and easily. The tools developed will also facilitate developers in doing UML modeling by accessing the network through a web-based internet application. With the web-based applications, the users require only a browser and an internet connection to use this application. This application also helps developers to understand of how to make UML diagrams correctly and good. In this research traditional methods Scrum model is used. Scrum method is Agile methods that is a process to cultivate software easily and can be developed in accordance with the development of information technology. Scrum is using empirical methods or in other words every stage in it involves inspection and adaptation.